The political economy of agricultural policy in Africa: Implications for agrifood system transformation - Resnick, Danielle (International Food Policy Research Institute, 2020)
The intent of this chapter is, first, to review how these components of political economy analysis have affected past agricultural policy decisions and, then, to highlight key points for building a broader empirical research agenda around agrifood system transformation. The first three sections of the chapter focus on how a political economy lens previously has been used to understand trade and price distortions, public investment patterns, and agro-industrial policies. Subsequently, the chapter emphasizes that the growing focus on agrifood system transformation implies an expanded array of needed interventions by the public sector that extend beyond the traditional mandates of agricultural ministries. Moreover, as the food system spans rural areas, small towns, and large cities, all of which are governed by different types of local authorities, public sector support for transformation is no longer under the domain of national governments alone. Consequently, the chapter argues that horizontal and vertical coordination— meaning cooperation across sectors and levels of government—will need to be addressed to manage the transformation process. Some examples of public sector restructuring initiatives are therefore discussed before the chapter concludes.